2011
DOI: 10.1111/j.1471-0307.2011.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterisation of enterocin KP produced by Enterococcus faecalis KP, a cheese isolate

Abstract: Enterococcus faecalis KP, a bacteriocin‐producing strain, was identified using 16S rRNA gene sequence homology (99%). Enterocin KP from E. faecalis KP was sensitive to papain and ß‐mercaptoethanol, but resistant to trypsin, pepsin, lipase, catalase, α‐amylase, organic solvents, detergents, EDTA and heat treatment (90°C/30 min). It was active at a wide pH range (2.0–8.0) and produced at maximum level in de Mann Rogosa Sharpe broth at 32°C with an inoculum amount of 0.1–1.0% and an initial pH of 5.5–7.5. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 46 publications
6
18
0
1
Order By: Relevance
“…Brain Heart Infusion (BHI, Merck, Germany) broth was used for culturing L. monocytogenes ATCC 7644, and it was kept at -80 °C in BHI broth containing 20% glycerol. (ŞAHINGIL et al, 2011;ISLEROGLU et al, 2012). At the end of incubation, each culture was centrifuged (Beoco, Germany) at 7000×g for 20 min, and the supernatant was sterilized by membrane fi ltration (0.45 μm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain Heart Infusion (BHI, Merck, Germany) broth was used for culturing L. monocytogenes ATCC 7644, and it was kept at -80 °C in BHI broth containing 20% glycerol. (ŞAHINGIL et al, 2011;ISLEROGLU et al, 2012). At the end of incubation, each culture was centrifuged (Beoco, Germany) at 7000×g for 20 min, and the supernatant was sterilized by membrane fi ltration (0.45 μm).…”
Section: Methodsmentioning
confidence: 99%
“…lactis BZ and Enterococcus faecalis KP, from traditionally produced Boza and White cheese (ŞAHINGIL et al, 2011;ISLEROGLU et al, 2012). Lactococcin BZ produced by L. lactis spp.…”
mentioning
confidence: 99%
“…Starter kültür kullanılmaksızın geleneksel olarak üretilen Beyaz peynirden izole edilen Enterococcus faecalis KP tarafından sentezlenen enterosin KP'nin Listeria monocytogenes, L. ivanovii, Enterococcus faecium, E. faecalis gibi bazı gıda kaynaklı patojen bakterilere karşı antimikrobiyal aktiviteye sahip olduğu belirlenmiştir [19]. Bu çalışmanın amacı enterosin KP'nin inhibitör aktivitesi üzerine pH ve NaCl'ün etkisini belirlemektir.…”
Section: Introductionunclassified
“…Enterococcus faecalis KP was used as enterocin KP producer strain (Isleroglu et al, 2012). Salmonella Typhimurium RSSK 95091 and E. coli O157:H7 RSKK 232 were supplied by the Refik Saydam Hıfzıssıhha Culture Collection (Turkey).…”
Section: Organisms and Culture Conditionsmentioning
confidence: 99%
“…Enterocin KP produced by Enterococcus faecalis KP exhibits bactericidal activity against some of the gram-positive pathogenic and spoilage bacteria such as Listeria monocytogenes, L. ivanovii, E. faecium, and E. faecalis (Isleroglu et al, 2012). Researchers reported that enterocin KP did not cause a clear inhibition zone against E. coli O157:H7 or Salmonella Typhimurium on BHI agar.…”
Section: Introductionmentioning
confidence: 99%